2013
DOI: 10.1002/jso.23322
|View full text |Cite
|
Sign up to set email alerts
|

Tumor size increase following preoperative radiation of soft tissue sarcomas does not affect prognosis

Abstract: Our results indicate that a 20% increase in tumor size following preoperative radiotherapy did not result in a worse outcome for patients when compared to those who had stable or decrease local tumor size following preoperative radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
0
9
0
1
Order By: Relevance
“…Reduction of tumour volume on the other hand obviously reflects the response to treatment, although intratumoural bleeding may contribute to a stable or increasing volume and MRI sequences specific for the detection of tissue haemorrhage may be useful in this setting. Two previous studies failed to show any significance of tumour volume increase on survival [ 5 , 6 ], and tumour volume reduction may be a more accurate marker. Tumour response using the RECIST criteraia was not prognostic, most probably because they are more blunt and minor volume changes are not recorded as a response.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Reduction of tumour volume on the other hand obviously reflects the response to treatment, although intratumoural bleeding may contribute to a stable or increasing volume and MRI sequences specific for the detection of tissue haemorrhage may be useful in this setting. Two previous studies failed to show any significance of tumour volume increase on survival [ 5 , 6 ], and tumour volume reduction may be a more accurate marker. Tumour response using the RECIST criteraia was not prognostic, most probably because they are more blunt and minor volume changes are not recorded as a response.…”
Section: Discussionmentioning
confidence: 89%
“…Tumour necrosis may be an objective measure of the effect of preoperative radiotherapy but there is no proof of its validity as a prognostic factor [ 4 ]. The use of radiologic measures is also questionable [ 5 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of 99 patients with STS treated with neoadjuvant or palliative RT has shown that in 58 patients, the tumor volume changed significantly with a volume increase in the majority of cases [111]. Moreover, a decrease in tumor size may be correlated with the presence of viable sarcoma cells, whereas "pseudoprogressing" tumors might be related to an extensive pathological response [79,112]. Thus, conventional response evaluation criteria in solid tumors (RECIST 1.1) should not be used to assess the response to neoadjuvant treatment in STS, except for myxoid liposarcomas.…”
Section: Radiologicalmentioning
confidence: 99%
“…23 In particular, sarcomas are challenging because an increase in size often does not indicate poor response to therapy. 24 Often, preoperative radiotherapy causes hemorrhage or necrosis leading to tumor enlargement. An increase in tumor size (≤ 20%) observed after radiotherapy but prior to surgery has not been associated with worse outcomes.…”
Section: Nuclear Medicinementioning
confidence: 99%
“…An increase in tumor size (≤ 20%) observed after radiotherapy but prior to surgery has not been associated with worse outcomes. 24 PET/CT can also be used to guide biopsy. Soft-tissue sarcomas are often heterogenous on MRI, with areas of necrosis or myxoid components.…”
Section: Nuclear Medicinementioning
confidence: 99%